Alcohol consumption and the risk of alcohol related cirrhosis in women. Issue 6590 (11th July 1987) - Norton, R; Batey, R; Dwyer, T; MacMahon, S
Abstract : The risks in women of cirrhosis with a likely primary alcohol aetiology were estimated for various levels of alcohol consumption in a case-control study. Data were obtained from 41 women with a first diagnosis of cirrhosis who had no evidence of non-alcohol-related cirrhosis; three matched controls were interviewed for each case. Significant increases in the risk of cirrhosis were detected at levels of consumption between 41 and 60 g daily; above this level a dose-response relation was observed. The risk of cirrhosis did not appear to be influenced by other nutritional factors or history of liver disease or use of hepatotoxic drugs. One per cent of Australian women consume more than 40 g alcohol daily, yet more than 90% of women identified with cirrhosis consumed alcohol at this level. Preventive interventions to reduce alcohol consumption in the small group of women who consume more than 40 g daily have the potential to reduce substantially the incidence of alcohol related cirrhosis.